In-season nutritional profile of two elite male basketball and volleyball teams - Balabinis, C.; Poulos, S.; Bizas, G.; Fevga, A. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The purpose of this study was to analyse and compare the nutritional profile of two male basketball and volleyball teams during the season. Findings: The findings of this study agree with previous literature. Athletes of both teams "suffer" from improper diet. Although they did not fall short of meeting the RDA values for iron, zinc, calcium, and magnesium, the quality and quantity of their dietary intake needs further improvement. In conclusion, athletes and training personnel should stop underestimating nutrition. They should realize the value and influence of a balanced diet on health and physical performance.